Formation of AlCl by radiative association - Andreazza, C. M. [UNESP]; Almeida, A. A. de; Vichietti, R. M. (Oxford Univ Press, 2018)
The rate coefficient for the formation of aluminium monochloride, AlCl, from the radiative association of aluminium and chlorine atoms is estimated as a function of temperature. The coupling of the Al and Cl atoms through the A(1)Pi molecular electronic state, which undergoes radiative transition to the X-1 Sigma(+) ground state, is the most efficient transition to form AlCl. The rate constant was found to vary with temperature according to the expressions k(T) = 1.22 x 10(-16)(T/300)(0.40) exp (-748/T) cm(3) s(-1) for temperatures between 300 and 1000 K, and k(T) = 2.20 x 10(-16)(T/300)(0.175)exp (-1067/T) cm(3) s(-1) for temperatures between 1000 and 14 000 K.
Keywords: atomic data; atomic processes; circumstellar matter; ISM: molecules